Utilization of Rice Straw for The Production of Bokashi Fertilizer in Nagari Koto Hilalang - Meriati; Alisa Sefani; Ersa; Hendri Faizal; Yosa Farman Buulolo; Hans Julpikar S; Alwi Burhan; Habib Burrahman; Redi Awala Putra; Yanda Govan (Pascasarjana Universitas Mataram, 2025)
This activity was carried out as part of the Community Empowerment Field Study Program (KKN-PPM). The purpose of this activity was to optimize the use of rice straw by processing it into bokashi fertilizer. This community service activity was carried out in Nagari Koto Hilalang, Kubung District, Solok Regency. The implementation method included the preparation stage (local materials: rice straw, manure, bran, rice husks, charcoal husks, sugar, and EM4; equipment: hoes, measuring cups, thermometers, and buckets), the fermentation implementation stage (training, monitoring fermentation), practical demonstrations, group discussions, the field application stage (the bokashi produced was applied to farmers' fields to test its effectiveness in improving soil fertility, and evaluation of harvest results). The result of this activity is bokashi fertilizer made from a mixture of straw, husks, bran, manure, sugar, and EM4. With this training, rice straw can be utilized optimally and sustainably. Bokashi fertilizer not only provides economic added value for farmers and local businesses, but also serves as an effective solution for maintaining soil fertility and reducing the environmental impact of straw burning. The production of bokashi fertilizer also encourages the development of micro and creative businesses, thereby improving community welfare and reducing dependence on chemical fertilizers.